Creating passionate learners engaging today's students for tomorrow's world - Brown, Kim M.; Frontier, Tony; Viegut, Donald (Clarity series, 2016)
Increase student engagement and create passionate learners. The path that leads a student to drop out of school is typically long, with engagement fading each year until the student stops attending. Clearly, increasing student engagement is the key to halting this sequence. But lack of consensus on the definition of "engagement" makes this difficult. What schools need is a common engagement literacy - a simple yet nuanced understanding of how to maximize engagement. This book offers the first comprehensive system for defining engagement and optimizing it in any student cohort. Inside, you'll learn: -- How to improve teacher feedback methods for maximum engagement -- The power of mindset (for both educators and students). -- Key vocabulary terms for furthering the engagement process. -- With this ..